Investigating the Role of Family Support Resources in Reducing Psychological Vulnerability after the Earthquake Crisis in Kermanshah - Saleh Salehi; Fahimeh Fadakardavarani; Zahra Amanollahi (Iranian Evolutionary Educational Psychology Journal, 2023)
Family support resources at all times have an effective role in supporting members and family structure to deal with various issues, especially in critical situations. Support resources are determined by the culture in each region and the expectations and meaning they give to these support resources. The family has undergone changes in recent years, and we need research to show whether the role of support resources has changed with these developments. The aim of this study was to determine the role of family support resources in decreasing the psychological vulnerability after the earthquake crisis in Kermanshah. The research sample was based on the purpose of the information saturation with 24 participants. Using semi-structured interviews, the experiences of families from the moment of the earthquake crisis were collected up to six months after that and with the grounded theory Analysis was made. Data analysis led to the extraction of support resources in five general categories including spatial-temporal resources, local-native resources, media resources, cultural-religious resources and related resources. According the results, family support resources can be used as a basis for reducing the psychological vulnerability of families in the crisis process and lead to a change in attitude and increase their compatibility.